ICSH guidelines for the standardization of bone marrow immunohistochemistry. (15th May 2015) - Torlakovic, E. E.; Brynes, R. K.; Hyjek, E.; Lee, S.‐H.; Kreipe, H.; Kremer, M.; McKenna, R.; Sadahira, Y.; Tzankov, A.; Reis, M.; Porwit, A.; the International Council for Standardization in Haematology
Summary Bone marrow (BM) tissue biopsy evaluation, including trephine biopsy and clot section, is an integral part of BM investigation and is often followed by ancillary studies, in particular immunohistochemistry (IHC). IHC provides in situ coupling of morphological assessment and immunophenotype. The number of different IHC tests that can be applied to BM trephine biopsies and the number of indications for IHC testing is increasing concurrently with the development of flow cytometry and molecular diagnostic methods. An international Working Party for the Standardization of Bone Marrow IHC was formed by the International Council for Standardization in Hematology (ICSH) to prepare a set of guidelines for the standardization of BM IHC based on currently available published evidence and modern understanding of quality assurance principles as applied to IHC in general. The guidelines were discussed at the ICSH General Assemblies and reviewed by an international panel of experts to achieve further consensus and represent further development of the previously published ICSH guidelines for the standardization of BM specimens handling and reports.